IL-13 and IL-33 Serum Levels Are Increased in Systemic Sclerosis Patients With Interstitial Lung Disease - Versace, Antonio Giovanni; Bitto, Alessandra; Ioppolo, Carmelo; Aragona, Caterina Oriana; La Rosa, Daniela; Roberts, William Neal; D'Angelo, Tommaso; Cinquegrani, Antonella; Cirmi, Santa; Irrera, Natasha; Navarra, Michele; Corrao, Salvatore; et al. (Frontiers in Medicine, 2022)
Objective: Systemic sclerosis (SSc) mortality is extremely variable according to internal organ involvement and it is due to pulmonary fibrosis in up to 30% of the cases. Animal models provide evidence that IL-33 is able to induce both cutaneous and pulmonary fibrosis via increased IL-13 and in SSc patients the levels of IL-33 correlate with skin fibrosis. Our aim was to test whether both IL-33 and IL-13 are higher in patients with diffuse SSc and interstitial lung disease (SSc-ILD) compared to SSc patients without ILD and healthy controls. Methods: Serum levels of IL-13 and IL-33 were measured in 30 SSc patients with diffuse disease and 30 healthy controls by enzyme-linked immunosorbent assay. The extent of pulmonary fibrosis was assessed according to HRCT Warrick score. Pulmonary function tests included lung diffusion capacity for carbon monoxide, forced vital capacity and total lung capacity. Results: Both IL-13 and IL-33 levels were increased in SSc patients compared to controls and significantly associated each other. DLco, FVC and TLC scores were inversely associated with IL-33 and IL-13 levels. Both IL-33 and IL-13 levels were significantly associated with the Warrick severity score and higher in the group of SSc patients with reduced pulmonary function compared to SSc patients with normal pulmonary function tests. Conclusion: The IL-13/IL-33 axis needs to be further explored in longitudinal studies to assess its validity as a biomarker and future treatment target, along with its downstream mediator ST2, in SSc-ILD patients.